Adolescent driving behavior before and during restrictions related to COVID-19. (September 2020) - Stavrinos, Despina; McManus, Benjamin; Mrug, Sylvie; He, Harry; Gresham, Bria; Albright, M. Grace; Svancara, Austin M.; Whittington, Caroline; Underhill, Andrea; White, David M.
Highlights: Post-COVID-19 restrictions, driving days per week decreased 37 % among adolescents. Vehicle miles driven in past two weeks decreased 35 % among adolescents. Decrease was lower among ethnic minorities, older and employed adolescents. Those with greater dire prosocial tendencies showed greater driving decline. Abstract: Introduction: Understanding who heeds the driving-related COVID-19 restrictions is critical for assisting public health professionals improve response to this and future pandemic events. The purpose of the current study was to characterize driving behavior changes among adolescents as a function of COVID-19 restrictions. It was hypothesized that adolescent driving would be reduced by COVID-19 restrictions, especially for younger teens, non-minorities, females, non-working teens, and those with higher prosocial tendencies. Methods: Participants were licensed drivers in "REACT, " a longitudinal study of adolescent driving attention. Upon enrollment in REACT, drivers were required to be age 16 or 18, have been issued a driver's license within the last two weeks, and be fluent in written/spoken English. The current observational cohort study was of drivers reporting driving exposure between February 8 and April 22, 2020. Linear mixed-effects models estimated differences in driving changes between COVID-19 periods. Results: Results indicated a decrease across pre-COVID-19 period (February 8 – March 13, 2020) in days driven per week and vehicle miles driven (VMD) was explained by the change of slope post-COVID-19 restrictions (March 14 – April 22, 2020). Post-COVID-19, driving days per week decreased by 37 % and VMD decreased by 35 %. This decrease was lower in ethnic minorities, older adolescents, and employed adolescents. Those with greater dire prosocial tendencies showed greater post-COVID-19 driving decline. Discussion: Findings provide early evidence of COVID-19 restriction-related adolescent driving changes suggesting older, employed, minority teens and teens with lower prosocial tendencies are less likely to reduce driving behavior. These observations provide a foundation for more extensive studies of adolescent drivers during various driving and contact restrictions and inform future public health campaigns for social distancing.